2011
DOI: 10.1371/journal.pone.0025222
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Accumulation in Glioblastoma with a Potential Role for Stem Cell Factor and Chemokine CXCL12

Abstract: Glioblastoma multiforme (GBM) is the most common and malignant form of glioma with high mortality and no cure. Many human cancers maintain a complex inflammatory program triggering rapid recruitment of inflammatory cells, including mast cells (MCs), to the tumor site. However, the potential contribution of MCs in glioma has not been addressed previously. Here we report for the first time that MCs infiltrate KRas+Akt-induced gliomas, using the RCAS/TV-a system, where KRas and Akt are transduced by RCAS into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…Tumor-secreted CXCL12 recruits peripheral endothelial progenitors to mitotic neovasculature, where the microenvironment influences the differentiation of endothelial progenitors [76]. Consistent with these findings, CXCL12 enhances the release of VEGF from CSCs, leading to tumor-growth-induced angiogenesis [77]. These studies suggest that tumor-associated CXCL12 is an important niche signal for the growth of GBM CSCs (Figure 3).…”
Section: Niche-dependent Signaling Of Cxcl12mentioning
confidence: 75%
“…Tumor-secreted CXCL12 recruits peripheral endothelial progenitors to mitotic neovasculature, where the microenvironment influences the differentiation of endothelial progenitors [76]. Consistent with these findings, CXCL12 enhances the release of VEGF from CSCs, leading to tumor-growth-induced angiogenesis [77]. These studies suggest that tumor-associated CXCL12 is an important niche signal for the growth of GBM CSCs (Figure 3).…”
Section: Niche-dependent Signaling Of Cxcl12mentioning
confidence: 75%
“…Immunofluorescent staining was carried out as described elsewhere (Lindberg et al., 2009; Polajeva et al., 2011) employing primary antibodies against human MC tryptase, hTPS (sc‐33676) and pSTAT5 (sc‐11671, Santa Cruz Biotech, Santa Cruz, USA) and chicken anti‐goat Alexa 488 and donkey anti‐mouse Alexa 555 (Invitrogen, Carlsbad, USA) as secondary antibodies. Identification and quantification of human MCs co‐expressing pSTAT5 was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Neutralizing experiments were performed in triplicates as described previously (Polajeva et al., 2011) using two MIF antibody concentrations (50 and 0.5 μg/ml; R&D Systems, Abingdon, UK) and control IgG (50 μg/ml; R&D Systems, Abingdon, UK). The selection of concentration range for MIF neutralizing antibodies was based on previous publications (Bernhagen et al., 2007; Ferro et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that CXCR4 is expressed on eosinophils [86] and concentrations of SDF-1 correlates with eosinophil recruitment [87]. It is known that SDF-1/CXCR4 signaling has pivotal role in mast cell (MC) recruitment in tumor tissue [88] and that MC produce proangiogenic chemokines in response to SDF-1 [89]. CXCR4+ dendritic cells (DC) promote angiogenesis during embryo implantation in mice [90] and CXCR4 is known as a critical chemokine receptor for migration of plasmacytoid DC [91].…”
Section: Sdf-1 As a Key Regulator Of Vessel Developmentmentioning
confidence: 99%